2016
DOI: 10.1021/acs.joc.6b02086
|View full text |Cite|
|
Sign up to set email alerts
|

Asymmetric Synthesis of Apratoxin E

Abstract: An efficient method for asymmetric synthesis of apratoxin E 2 is described in this report. The chiral lactone 8, recycled from the degradation of saponin glycosides, was utilized to prepare the non-peptide fragment 6. In addition to this "from nature to nature" strategy, olefin cross-metathesis (CM) was applied as an alternative approach for the formation of the double bond. Moreover, pentafluorophenyl diphenylphosphinate was found to be an efficient condensation reagent for the macrocyclization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The synthetic route of 1 is depicted in Scheme . We applied a similar synthetic strategy that we previously developed for the synthesis of apratoxins S4–S9, , which is a modification of other published methods. Recently, some other papers were published on total syntheses of apratoxins. The known compounds 2 , 3 , and 7 were synthesized as we established previously . The N -Boc group in 3 was selectively removed with TMSOTf in the presence of 2,6-lutidine, which was subsequently followed by a coupling reaction of deprotected 3 with 2 to afford compound 4 in 92% yield.…”
mentioning
confidence: 99%
“…The synthetic route of 1 is depicted in Scheme . We applied a similar synthetic strategy that we previously developed for the synthesis of apratoxins S4–S9, , which is a modification of other published methods. Recently, some other papers were published on total syntheses of apratoxins. The known compounds 2 , 3 , and 7 were synthesized as we established previously . The N -Boc group in 3 was selectively removed with TMSOTf in the presence of 2,6-lutidine, which was subsequently followed by a coupling reaction of deprotected 3 with 2 to afford compound 4 in 92% yield.…”
mentioning
confidence: 99%
“…Total syntheses of apratoxin A ( 1a ) and its analogues have been reported previously. ,,,, Forsyth et al accomplished the first total synthesis of 1a , , and several groups including the present authors have since reported the synthesis and SAR studies of apratoxins and their analogues using solution-phase ,,, or solid-phase syntheses. , However, the syntheses of apratoxins and their analogues require multistep processes and result in very low overall yields. In addition, apratoxins are sensitive to acidic conditions , and have a Michael acceptor in the moCys moiety .…”
Section: Introductionmentioning
confidence: 77%